Clinical Profile and Treatment Outcome of Patients with Trigeminal Neuralgia: A Retrospective study in a Tertiary Hospital of Eastern Nepal - Maharjan, Iccha Kumar; Rimal, Jyotsna; Subedi, Asish; Regmee, Pragya (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: Neuropathic orofacial pain is common non-dontogenic pain. Diagnosis relies primarily on history taking with less of pathologic change visible. Trigeminal neuralgia (TGN) is a common neuropathic pain affecting the maxillofacial region of fifth cranial nerve (V). Objective: To assess clinical characteristics, effective therapeutic regimen, side effect, radiographic and laboratory investigation in Trigeminal neuralgia patients. Methods: Retrospective study included all patients visiting the department with records from 2014 to 2021. After ethical approval for study, eighty patients were diagnosed based on ICHD3 criteria. Patient with atypical feature with sensory deficit underwent CT OR MRI to rule of mass or lesion along the cerebello-pontine angle recess and other organic cause. The data were analysed using SPSS version 11.5 and Microsoft Excel 2017. Results: A total of 80 patients were retrieved. The common side affected were right 46 (57.5%) followed by left 28 (35%), bilateral four (5%) and anterior region two (2.5%). The most common branch involved was mandibular followed by maxillary branch and combination. Management was primarily done by carbamazepine (CBZ) or in combination. Common side effects were drowsiness, dizziness, nausea and diplopia. CT scan and MRI showed space occupying lesion in three cases. Refractory cases underwent neurolysis and symptomatic and few classical TGN cases were sent for surgical management. Conclusions: Diagnosis of Trigeminal neuralgia is primarily based on clinical characteristic due to high cost and unavailability of imaging and nerve testing. Treatment is by single or multiple drugs with adjunct therapy.